Retrospective Survey of Amphibian Pathology Cases at Texas A&M University System (2016–2020). (May 2021) - Balamayooran, Gayathriy; Snook, Eric; Tocidlowski, Maryanne; Flanagan, Joe; Sims, Will; Helman, Gayman; Hensel, Martha; Hodo, Carolyn L; Templeton, Alexis A.; Anguiano, Maritza; Edwards, Erin E.; Hoffman, Jay; et al.
Summary: Dramatic declines in amphibians worldwide highlight the need for a better understanding of diseases affecting these species. To delineate the health issues of amphibians submitted to Texas A&M University System (2016–2020), the databases were queried on the basis of defined selection criteria. A total of 502 anurans (157 frogs [44 species] and 345 toads [10 species]) and 30 caudatans (23 salamanders [6 species] and 7 newts [4 species]) were reviewed. A most likely cause of death or major pathological finding (CD-MPF) leading to euthanasia was identified in 295 (55%) Anura cases and 15 (50%) Caudata cases. Of the 532 records reviewed, anurans included 492 captive, seven free-ranging and three undetermined specimens. All caudatans were captive. The most common CD-MPF in anurans was infectious/inflammatory (228/295; 77%), involving mycobacteriosis (73/228; 32%), chlamydiosis (44/228; 19%) and mycosis (32/228; 14%). Neoplasia was less common (28/295; 9%). Infectious/inflammatory lesions (14/15; 93%) were the main CD-MPFs in caudatans. Infectious diseases are a significant threat to captive amphibians in Texas and these results may aid personnel involved in amphibian conservation programmes, veterinarians and diagnosticians.